Візія українця як Іншого у польському літературному дискурсі - Вознюк, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article studies the reception of Ukrainians in Polish literary discourse which developed through the centuries. The conclusion can be made that nowadays in Polish writings the stereotype of colonial view point on the image of Ukrainian people has reduced.